HR DEVELOPMENT: Empowerment Strategy in Improving Employee Performance - Jalil, Rahmat (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Empowerment of human resources is very significant, strategic and comprehensive for each process of organizational activity in realizing the performance as expected. This study aims to identify, analyze and examine the practice of employee empowerment strategies implemented by PT. Jaya Initiative. Thus this research uses qualitative research methods through observation, interviews, documentation studies and FGD. Processed data was obtained from secondary data obtained from internet sites from credible institutions/institutions while primary data was obtained from observation, in-depth interviews and documentation. The results showed the employee empowerment strategy in an effort to improve employee performance at PT. Jaya Prakarsa has not run optimally, empowerment is only limited to developing competence, developing organizational culture and giving authority so that it needs to be studied more deeply.